Identification Of Mycorrhizal Fungi Arbuscular Indigenous On Various Land Use Patterns - Karyaningsih, Ika; Ai Nurlaila; Dede Kosasih; Wiwit Walinda; Fika Fauziah (Journal of Tropical Mycorrhiza, 2025)
Information on the existence of indigenous Arbuscular Mycorrhizal Fungi (FMA) is needed as an early stage of FMA biofertilizer production to overcome the scarcity of subsidized fertilizers. The purpose of this study was to determine the type of indigenous FMA and determine the location that can be used as a source of FMA inoculum as a biological fertilizer material. Soil and root samples were observed in 4 types of land use, with 10 repeats. The results showed that for every 100 g of soil, the highest number of spores were found in natural forest types as many as 248 spores, in agroforestry land 138 spores, in ex-mining land 95 spores, and at least in sweet potato-intensive agricultural land only 58 spores. Natural forest areas have a high enough spore count so that natural forest locations have the potential to be a source of indigenous FMA inoculum than other types of land use. There are three genera of FMA found, namely Glomus, Gigaspora, and Acaulospora. Glomus is found on all types of land use except monoculture farmland and is the genus that dominates spore populations. The genus Acaulospora is found only in agroforestry land types. Indigenous FMA was found to be able to infect plant roots in natural forests in as much as 6 % and agroforestry land in as much as 16 % so it was included in the medium and low categories. Meanwhile, in the monoculture type of sweet potato and ex-mining land, no root infection was found.